Pengaruh Insiden Stress terhadap Motivasi Penyusunan Skripsi di Masa Pandemi Covid-19 - Siswoto Hadi Prayitno; Sumarman Sumarman (Jurnal Ilmiah Kesehatan Rustida, 2021)
The Covid-19 pandemic period is a stressful time felt by most students, this happens because of new habits that must be carried out strictly so as not to be exposed to the Covid-19 virus. This stress affects students in carrying out the learning process and can reduce motivation in doing thesis. The purpose of this research is to find out the influence of the incidence of stress and motivation in the preparation of the thesis. The research method is a non-experimental quantitative descriptive correlational type. This research was conducted at the Rustida Health Academy with the research sample being the sixth semester students of the DIII Nursing Study Program with a total sample of 74 students. Data were obtained using the Stress Analysis questionnaire in this study using the depression anxiety stress scale 42 (DASS 42) by Lavibond & Lavibond. While the motivation score using the Motivated strstegies of learning Questioner (MSLQ) method with the Krukall Walss test p 0.158 > 0.05. The results showed that there was no effect of the incidence of stress on the motivation for writing the thesis of the sixth semester students of the DIII Nursing Study Program for the 2019-2020 Academic Year. The conclusion is that the stress experienced by most of the students is at a moderate level and the motivation in working on the thesis is high.